2014
DOI: 10.4141/cjps2013-281
|View full text |Cite
|
Sign up to set email alerts
|

Combining resistance to common bacterial blight, anthracnose, and bean common mosaic virus into Manitoba-adapted dry bean (Phaseolus vulgaris L.) cultivars

Abstract: Boersma, J. G., Conner, R. L., Balasubramanian, P. M., Navabi, A., Yu, K. and Hou, A. 2014. Combining resistance to common bacterial blight, anthracnose, and bean common mosaic virus into Manitoba-adapted dry bean (Phaseolus vulgaris L.) cultivars. Can. J. Plant Sci. 94: 405–415. Resistance to common bacterial blight (CBB) is generally absent in dry bean cultivars. In order to transfer CBB resistance into dry bean cultivars grown in Manitoba, crosses were made between CBB-resistant navy bean OAC Rex and suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The presence of SU91 was associated with a reduced incidence of leaf infection in most of the lines, but not in HR67 or F4GR1. Boersma et al (2014) demonstrated that there was a close correlation between field ratings for CBB and the presence of SU91. However, Duncan et al (2012) determined that under severe disease pressure, SU91 alone did not provide high levels of CBB resistance and the combination of SU91 and BC420 was associated with high levels of CBB resistance.…”
Section: Qtl Markersmentioning
confidence: 86%
See 1 more Smart Citation
“…The presence of SU91 was associated with a reduced incidence of leaf infection in most of the lines, but not in HR67 or F4GR1. Boersma et al (2014) demonstrated that there was a close correlation between field ratings for CBB and the presence of SU91. However, Duncan et al (2012) determined that under severe disease pressure, SU91 alone did not provide high levels of CBB resistance and the combination of SU91 and BC420 was associated with high levels of CBB resistance.…”
Section: Qtl Markersmentioning
confidence: 86%
“…The navy bean cultivar 'OAC Rex', which also used tepary bean as the CBB resistance source, was registered in 2002 (Michaels et al 2006) as the first Canadian CBBresistant cultivar. The Simple Sequence Repeat (SSR) marker PVctt001 (Yu et al 2000b) on Pv04 was shown to be associated with resistance to CBB in the navy bean cultivar OAC Rex (Michaels et al 2006;Boersma et al 2014).…”
mentioning
confidence: 99%
“…OAC Rex was developed from interspecific hybridization of tepary and common beans and had a moderate resistance to CBB. The genotype is known to carry a major QTL linked to scar marker SU91 on chromosome Pv08 [ 23 , 24 , 32 , 67 ]. OAC Rex was used as a parent for many CBB-resistant breeding lines and the recently released genotype Lighthouse [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the necessity of using resistant varieties, plant breeders need to investigate sources of BCMV resistance in response to the challenges of common bean susceptibility. Several studies have been conducted to evaluate the existence of disease-resistant genotypes ( Mukeshimana et al, 2005 ; Bello et al, 2014 ; Boersma et al, 2014 ; Yeken et al, 2018 ; Palacıoğlu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%